Acesso à informação e transparência ativa no portal do Instituto Federal de Educação, Ciência e Tecnologia do Pará - ASSUNÇÃO, Renato Vieira da (2021)
The research sought to analyze the applicability of the Law on Access to Information and active transparency in the Portal of the Federal Institute of Education, Science and Technology of Pará. The guidelines of Law 12.527/2011 and Decree 7.724 /2012 establish standards for public institutions related to the concept of active transparency. Based on this concept, the organs and entities of the public administration have the duty to inform the society in a proactive and spontaneous way, about its management and its acts, through the dissemination of public information produced or guarded by them. In this way, regardless of request, the disclosure of this information must be carried out through institutional websites in a clear and objective manner in citizen language, avoiding that they may have their understanding compromised by the use of little known nomenclatures or technical terms. Seven years after the regulation of these guidelines, the specialized literature has pointed out that a significant part of public institutions has failed to comply with the legislation on access to information, in particular, under the prism of active transparency. In this way, this research had the specific objectives of verifying if the portal of the Federal Institute of Pará complies with the guidelines of active transparency and, if the archival information is being made available in an understandable and practical way, as determined by the Law on Access to Information and Decree 7.724/12. In order to achieve this, ten indicators and / or requirements were established based on the legislation and recommendations of the Office of the Comptroller General of the Union. In addition, a service level scale was established, which: the requirement could be met in whole or in part or not. The result obtained by the research corroborates with what is presented in the literature, of the requirements established by this work, the Federal Institute of Education, Science and Technology of Pará fully answered 60% of them, failing to meet 30% and partially attending 10%. In this way, the Institution presents a high degree of noncompliance with the legal guidelines for access to information and active transparency.